Investigation into the metabolism of 1,8-cineole in an intestinal cell culture model and acquisition of its immune-modulatory effect via gene expression analysis - Müller, Jakob; Gruner, Natalie; Almstätter, Isabella; Kirsch, Frauke; Büttner, Andrea; Pfaffl, Michael (Flavour and Fragrance Journal, 2012)
1,8-Cineole, a common and widely used odorant with antiphlogistic and anti-inflammatory properties, was investigated in this study with regard to potential physiological effects targeting mainly its intestinal effects. Accordingly, the aim of the study was to utilize a combinatory methodological approach to both monitor potential biotransformatory effects on a chemo-analytical basis, as well as physiological and immunological tools to monitor further effects of biofeedback. Reverse transcription quantitative real-time polymerase chain reaction was used to monitor the occurrence of relative expression changes for particular marker genes, following 1,8-cineole treatment. Furthermore, a potential effect of 1,8-cineole on the proliferation and fitness of the intestinal cells using impedance sensing was studied. Generally, our studies showed that the applied model system did neither lead to any significant metabolite formation, nor did the applied dosages result in any major modifications with regard to gene expression. Also, it was shown that cineole had no effect on the intestinal porcine epithelial cells applied in pharmacological or physiological concentrations; neither during the attachment and spreading process nor on confluent cell layers. Only the exposure to high concentrations of cineole (> 1g/l) affected the cells and led to massive cell detachment. Overall, our studies show that even common higher 1,8-cineole dosages do not seem to lead to any major physiological or aversive response, only until a critical concentration is reached that then directly leads to cell death within the intestinal model. © 2012 John Wiley & Sons, Ltd.
UnivIS-Import:2015-03-09:Pub.2012.nat.dchph.llmch.invest
Keywords: ECIS; Gas chromatography-mass spectrometry; Hydroxycineole; Metabolism; RT-qPCR; Stable isotope dilution assay